REVIEW DESAIN JARINGAN TATA AIR RAWA PADA KAWASAN TANJUNG PERENGAT KABUPATEN BERAU Diajukan oleh - ASWARI, DENI (KURVA S JURNAL MAHASISWA, 2014)
East Kalimantan's economy is currently dominated by economy basedexploitation of natural resource that can not be renewd, frpm the Gross RegionlaDomestic Product (GDP) in 2012 amounted to 390.63 is dominated by the miningsector amounted to 50.79 %, while the srgicultural sector accounted for only 5,35%. of course this is not the structure of the economy is expected by the ProvincialGovernment of East Kalimnatan because believe the economy theta rely eklpoitasiwater resources can not be renewe in the near future will decline rapidly as theexhaustion of reserves of water resources.Region of Tanjung Perengat is a region area of swap areas of potentialfor rice farming, due to the design of the network layout swamp water in the areaof cape Perengat are manya that can not be used again it will be conducted toreview the network design the water system in the area headland Perengat is to beuseful for the regional area of rice farming.In reneral from the Cape region of swamps survey area is relatively flatPerengat, which is an area of tidal marsh, where the influence of the tidal reach themost remote areas. Of teh total area covers approximately 2.000 hectares, the typeof land use in the survey area Tanjung Perengat marsh dominated by rice paddies,fields, rubber plantation and the rest are shrubs. Based on the results of laboratoryanalysis, soil fertility level in the survey area swamp Tanjung Perengat generallyis classified as moderate